Effort Estimation in BPMS Migration - Christopher Drews; Birger Lantow (Complex Systems Informatics and Modeling Quarterly)
Usually Business Process Management Systems (BPMS) are highly integrated in the IT of organizations and are at the core of their business. Thus, migrating from one BPMS solution to another is not a common task. However, there are forces that are pushing organizations to perform this step, e.g. maintenance costs of legacy BPMS or the need for additional functionality. Before the actual migration, the risk and the effort must be evaluated. This work provides a framework for effort estimation regarding the technical aspects of BPMS migration. The framework provides questions for BPMS comparison and an effort evaluation schema. The applicability of the framework is evaluated based on a simplified BPMS migration scenario.